Complete response to pembrolizumab in recurrent nested variant of urothelial carcinoma. Issue 5 (24th June 2021) - Fukuta, Kyotaro; Izaki, Hirofumi; Shiozaki, Keito; Nakanishi, Ryoichi; Inai, Tohru; Kataoka, Hideyuki; Kudo, Eiji; Kanda, Kazuya
Abstract : Introduction: The nested variant of urothelial carcinoma is rare and shows poor prognosis. We report a case of complete response to pembrolizumab in recurrent nested variant. Case presentation: A 50‐year‐old man visited another hospital with hematuria and weight loss. Clinical stage T4aN0M0 bladder cancer and acute renal failure were diagnosed. He was referred to our hospital and underwent radical cystectomy. Histological examination showed pathological stage T4aN2 nested variant of urothelial carcinoma. He received 3 cycles of gemcitabine and carboplatin adjuvant chemotherapy. However, para‐aortic lymph node metastasis appeared 7 months after cystectomy. He received pembrolizumab as systemic chemotherapy. After 10 cycles, the lesion remained undetectable and we evaluated the response as complete. He has received 18 cycles in total and no recurrences or metastases have been observed. Conclusion: Pembrolizumab may offer effective treatment for nested variant of urothelial carcinoma.